Therapeutic effect of double-filtration plasmapheresis combined with methylprednisolone to treat diffuse proliferative lupus nephritis - Li, MinXia; Wang, YuanDa; Qiu, Qiang; Wei, RiBao; Gao, YuWei; Zhang, Li; Wang, Yong; Zhang, XueGuang; Chen, XiangMei (Journal of clinical apheresis, 2016)
Objective: The efficacy of double‐filtration plasmapheresis (DFPP), combined with methylprednisolone, to treat diffuse proliferative lupus nephritis (LN) was studied. Methods: Twenty‐four patients who were admitted to the hospital and diagnosed with diffuse proliferative LN (LN Class IV‐G(A)) through renal biopsy from 2011 to 2013 were recruited as the study subjects. The patients' clinical manifestations were nephritic syndrome and/or renal insufficiency. The pathological features were glomerular diffuse proliferative lesions. The patients were divided into two groups: the treatment group and the control group, with 12 patients in each group. The patients in the treatment group were first treated with DFPP combined with methylprednisolone (0.8–1.0 mg/kg/day); subsequently, they were put on methylprednisolone therapy only. The patients in the control group were first put on methylprednisolone pulse therapy (500–1,000 mg) for 3 days; subsequently, they were treated with methylprednisolone (0.8–1.0 mg/kg/day) combined with mycophenolate mofetil (1.5 g/day). The patients were observed for 24 months. Levels of hemoglobin, platelet, albumin, serum creatinine, 24‐h urinary protein, serum C3, antinuclear antibody (ANA), anti‐dsDNA, and anti‐Smith were measured at 0, 3, 6, 12, and 24 months. Complete remission and recurrence standards were established. The total dosages of methylprednisolone were calculated. Repeated renal biopsy was performed on several patients. Results: There was no statistical significance in the baseline conditions of the treatment and the control groups. For the treatment group, no plasmapheresis‐related complications occurred. The two groups showed no significant difference in complete remission. The patients' edema and serous effusion resolved, urine volume, serum creatinine, and albumin levels returned to normal, urine protein decreased in treatment group more rapidly than the patients in the control group. The mean dose of methylprednisolone received in the treatment group was lower than in the control group. The complement C3 levels in the treatment group were significantly higher than in the control group. The recurrence rate in the treatment group was lower than in the control group. Repeated renal biopsies on several patients in the treatment group indicated that their pathology improved significantly, changing from LN (IV) to LN(II–III). Conclusions: Appropriate application of DFPP combined with glucocorticoid therapy could accelerate the remission of diffuse proliferative LN, reduce overall glucocorticoid dosage, prevent recurrence, and maintain C3 level in a higher level. J. Clin. Apheresis 31:375–380, 2016. © 2015 Wiley Periodicals, Inc.